Systematic Literature Review: Improving Self Regulated Learning Through The Flipped Classroom Model Based on Interactive E-Books - Ainulluluah Ainulluluah; Endry Boeriswati; Yuli Rahmawati; Bramianto Setiawan (Universitas Pahlawan Tuanku Tambusai, 2022)
In the flipped classroom, students must have independent learning behavior to achieve optimal competence. However, the reality is that students' independence in learning is not good, so a teacher is supposed to carry out knowledge that can facilitate the formation of student learning independence. One of the lessons that can increase students' learning independence is the Flipped Classroom model with the help of interactive e-books. This study aims to conduct a literature review on the importance of improving student learning independence through the Flipped Classroom model based on Interactive e-books. The SLR (Systematic Literature Review) method was chosen in this study. Data collection was carried out by documenting and reviewing all articles on learning independence that had similar research in this report. A total of 15 journal articles obtained from Google Scholar with the help of the publish and perish application were used in this study. Based on the literature review, it can be concluded that increasing the ability to learn independently is needed by students in learning, especially in online education with the interactive e-book-based flipped classroom model. Independent learning has a positive influence on students in education.